2007
DOI: 10.1007/s10158-007-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

The cys-loop ligand-gated ion channel gene family of Brugia malayi and Trichinella spiralis: a comparison with Caenorhabditis elegans

Abstract: Nematode cys-loop ligand gated ion channels (CLGIC) mediate neurotransmission and are important targets for anthelmintics in parasitic nematodes. The CLGIC superfamily in nematodes includes ion channels gated by acetylcholine, gamma-amino butyric acid (GABA), glutamate, glycine and 5-HT. The macrocyclic lactones and the nicotinic agonists are important groups of anthelmintics that target the glutamate gated chloride channels and the nicotinic acetylcholine receptors, respectively. The model organism Caenorhabd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 56 publications
2
78
1
Order By: Relevance
“…A homology search revealed four possible GluCl subunits in B. malayi (16). Phylogenetic analysis and naming according to Beech et al (19) allowed us to infer that these subunits are orthologs of the GLC-2, GLC-4, AVR-14A, and AVR-14B subunits in C. elegans and other nematodes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A homology search revealed four possible GluCl subunits in B. malayi (16). Phylogenetic analysis and naming according to Beech et al (19) allowed us to infer that these subunits are orthologs of the GLC-2, GLC-4, AVR-14A, and AVR-14B subunits in C. elegans and other nematodes.…”
Section: Resultsmentioning
confidence: 97%
“…1073/pnas.1011983107/-/DCSupplemental. reveals only four subunits, two of them (AVR-14A and AVR-14B) related to IVM-sensitive channels (15,16).…”
mentioning
confidence: 99%
“…vertebrates (Möhrlen et al 2006), many of which demonstrate essential developmental functions including digestion, hatching, embryogenesis, processing of the extracellular matrix, skeleton formation and morphogenesis (Bond and Beynon, 1995). The astacin metalloproteases have also been found to have crucial developmental roles in a wide range of freeliving and parasitic nematodes, including C. elegans (Hishida et al 1996;Möhrlen et al 2003;Davis et al 2004;Novelli et al 2004;Suzuki et al 2004;Park et al 2010), O. volvulus (Borchert et al 2007), H. contortus (Gamble et al 1989;Stepek et al 2010b), A. caninum (Williamson et al 2006) and S. stercoralis (Gallego et al 2005). In general, the C. elegans astacins are associated with tissues exposed to the external environment and have diverse functions which, in part, relate to unique nematode-specific extracellular structures, such as the eggshell, the cuticular exoskeleton and the cuticular pharyngeal grinder (Park et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, NAS-36 may be essential for cuticle ecdysis in parasitic nematodes and suggests a degree of redundancy in the C. elegans astacin family. Williamson et al (2007) indicated potential gene redundancy in proteins that belong to the Cys-loop ligand gated ion channels family, with a larger gene family in C. elegans in comparison to B. malayi and Trichinella spiralis. Another nematode astacin metalloprotease of subgroup V, NAS-34, is necessary for normal hatching of the embryo of C. elegans (Hishida et al 1996).…”
Section: Hc Nas-36mentioning
confidence: 99%
See 1 more Smart Citation